Changeling - Ritter, William, 1984- (Ritter, William, 1984- Oddmire, 2019)
Twelve-year-olds Tinn and Cole, raised as human twins in sleepy Endsborough, risk their lives in the Wild Wood, Oddmire Swamp, and the Deep Dark to learn which is a goblin changeling with an important mission.